Increasing Competitiveness of Passenger Rail Transportation Amid Organizational and Structural Transformations - V.Myroshnychenko, U; V.Motsna, I; V.Gritsenko, N (International Journal of Engineering and Technology, 2018)
The decline in the volume of passenger traffic, the critical level of financial condition, and the depreciation of the material and technical base caused a significant economic downfall of the railway transport. The reorganization of structural units is intended to improve the quality of service provision, which affects the final demand of consumers, which influences the volume and profitability of passenger transportation. The author suggests applying the principles of the organization of the revenue account from passenger transportation, exempt from VAT, to reduce its loss ratio amid organizational and structural transformations during the reshaping of passenger transport segment. Increasing the competitiveness of passenger rail transportation will contribute to the economic development of the entire nation.Â Â